Meal of Mucuna deeringiana forage on some physiological microbial groups and fermentative indicators of the cecum of broiler chickens - Rodr?guez, Zoraya; Mart?nez, Madeleidy; Sarmiento, L.; P?rez, Mayrulis; Dihigo, Luis Enrique; N??ez, Odalis; Herrera, Felix Rafael; Hern?ndez, Yasmila (Cuban Journal of Agricultural Science, 2012)
An experiment was performed according to complete random design to determine the effect of including the meal of the Mucuna deeringiana forage on some physiological microbial groups and on the fermentative indicators of the cecum of broiler chickens. Sixteen male chickens (hybrid HE21) were used at a rate of four chickens per treatment. The treatments were: the control, 5, 10, and 15 % of meal of mucuna forage to substitute the corn meal. At 42 d, the microbial groups (total bacteria, proteolytic bacteria, celullolytic bacteria, and fungi) and the fermentative indicators (SCFAt, ammonia, and pH) were determined. The total bacteria were reduced with 10 % of mucuna, and with 5 %, counts superior to 10-10 ufc mL-1 were attained. The counts of cellulolytic fungi were not affected, as compared with the control, but they differed between 5 and 10 %, being inferior in the latter (P < 0.05), whereas the celullolytic bacteria did not show differences between treatments. The proteolytic bacteria were superior (P < 0.05) with 10 %, but there were not differences in respect to the control (2.91 vs 2.33 x 10-6 cfu mL-1). The pH did not vary between treatments, the concentration of SCFAt was increased with the inclusion of mucuna, and a peak (82.32 meq L-1) was reached with 10 %, whereas the NH3, with 10 and 15 % of mucuna, showed lower concentrations, as compared with the rest of the treatments (P < 0.05). It was concluded that the inclusion of the meal of M. deeringiana forage increases the production of total SCFA; and, with the highest levels, it diminishes the ammonia in the ceca. In the microbial concentrations, there was not a defined performance being in correspondence with the fermentative indicators. Key words: mucuna, cecum microorganisms, fermentation products.